ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PASTA GIGI PEPSODENT - Rino Aji Kurniawan, 09.05.51.0038 (Students Journal of Economic and Management, 2013)
This study aimedtoanalyzethe relationshipbetween thequality of theproduct, priceandpromotionon purchase decisionsPepsodenttoothpaste. Object ofthis studyis theUniversity StudentStikubankSemarang. The population inthis studyis theUniversity StudentStikubankSemarang. Samples was done bypurposivesamplingmethod. withthis techniqueto select thosewhowillbe the respondentbased onspecific characteristicspossessedthesamplesconsideredto havenothing to dowiththe characteristics ofthe population thatis predetermined.Type ofdata usedisprimary data. The analysis techniqueusedin this studyis the technique ofmultiple linear regression analysis. The results ofthis study are: (1) the variablequality of theproductproved tohave asignificantpositiveinfluenceon purchase decisions, 2) variablepricesshown to haveaÂ Â  significantpositiveinfluenceon purchase decisions, (3) promotionvariablesshown to have asignificantpositiveinfluenceon purchasing decisions.Keywords: quality ofproduct, price, promotion, purchasing decisions